Use of gamification as collaborative learning resources - Concepción García, Nicanor (International Journal of Scientific Research and Management (IJSRM), 2021)
There is no doubt that students in contact with Information and Communication Technologies (ICT) benefit in various ways and advance in this new vision of the user of training. Gamification is a learning tool that is being used more frequently, and acquiring great relevance in the field of education, with the implementation and use of this support tool as a collaborative resource in a vital campus, it was proven that it is beneficial to improve the performance and quality of education in students who take the subject of Arithmetic and Geometry. At the ISOFODOSU.The purpose of this article is to present the results obtained from the intervention with students enrolled in the subject Arithmetic and Geometry in the academic periods September - December 2019, January - April 2020, on gamification in a virtual learning environment as a collaborative resource in combination with mobile devices. The objective set by the researcher is to check whether the use of this collaborative tool combined with mobile devices can improve academic performance, and increase the grades of students enrolled in the subject at the Salome Ureña Higher Institute of Teacher Training.